Adaptive pre‐specification in randomized trials with and without pair‐matching. (19th July 2016) - Balzer, Laura B.; van der Laan, Mark J.; Petersen, Maya L.
Abstract : In randomized trials, adjustment for measured covariates during the analysis can reduce variance and increase power. To avoid misleading inference, the analysis plan must be pre‐specified. However, it is often unclear a priori which baseline covariates (if any) should be adjusted for in the analysis. Consider, for example, the Sustainable East Africa Research in Community Health (SEARCH) trial for HIV prevention and treatment. There are 16 matched pairs of communities and many potential adjustment variables, including region, HIV prevalence, male circumcision coverage, and measures of community‐level viral load. In this paper, we propose a rigorous procedure to data‐adaptively select the adjustment set, which maximizes the efficiency of the analysis. Specifically, we use cross‐validation to select from a pre‐specified library the candidate targeted maximum likelihood estimator (TMLE) that minimizes the estimated variance. For further gains in precision, we also propose a collaborative procedure for estimating the known exposure mechanism. Our small sample simulations demonstrate the promise of the methodology to maximize study power, while maintaining nominal confidence interval coverage. We show how our procedure can be tailored to the scientific question (intervention effect for the study sample vs. for the target population) and study design (pair‐matched or not). Copyright © 2016 John Wiley & Sons, Ltd.